From a "planning-led regime" to a "development-led regime" (and back again?). The role of municipal planning in the urban governance of Stockholm. - Zakhour, Sherif; Metzger, Jonathan (Taylor & Francis, 2018)
Much recent research has pointed out the generally declining influence of planning on urban development, often explaining this trend with major structural shifts in the world economy. In this paper we take a somewhat different tack founded upon a "devil is in the detail" intuition. Tracing the city of Stockholm's urban governance landscape over the course of a century, we examine how overarching patterns of change are reflected in and reproduced through the organisation of local planning and development administrations. Our point is not to dispute the relevance of broader structural explanations, but rather to suggest that any ambition to change the currently dominant development-led regime must combine more general understandings of broad international trends with a detailed understanding of the concrete institutional mechanisms that come to produce specific patterns of effects at a particular time and place. The paper argues that for urban planning to be promoted as a governance of place, more research on identifying the critical institutional mechanisms which enable or constrain the realisation of particular policy goals is needed.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Entwicklungsplanung; Urban governance; Planung; Bedeutungsverlust; Steuerung; Planungsverständnis; Demokratisierung; Partizipation